Umbilical Cord Mesenchymal Stromal Cell-Derived Small Extracellular Vesicles Modulate Skin Matrix Synthesis and Pigmentation - Kee LT; Foo JB; How CW; Nur Azurah AG; Chan HH; Mohd Yunus MH; Ng SN; Ng MH; Law JX (International Journal of Nanomedicine)
Li Ting Kee,1 Jhi Biau Foo,2– 4 Chee Wun How,5 Abdul Ghani Nur Azurah,6 Hong Hao Chan,5 Mohd Heikal Mohd Yunus,7 See Nguan Ng,8 Min Hwei Ng,1 Jia Xian Law1 1Department of Tissue Engineering and Regenerative Medicine, Universiti Kebangsaan Malaysia, Cheras, Kuala Lumpur, Malaysia; 2School of Pharmacy, Taylor’s University, Subang Jaya, Selangor, Malaysia; 3Digital Health and Medical Advancements Impact Lab, Taylor’s University, Subang Jaya, Selangor, Malaysia; 4Non-Destructive Biomedical and Pharmaceutical Research Centre, Smart Manufacturing Research Institute, Universiti Teknologi MARA Selangor Campus, Puncak Alam, Selangor, Malaysia; 5School of Pharmacy, Monash University Malaysia, Bandar Sunway, Selangor, Malaysia; 6Department of Obstetrics and Gynaecology, Universiti Kebangsaan Malaysia Medical Centre, Kuala Lumpur, Malaysia; 7Department of Physiology, Universiti Kebangsaan Malaysia, Kuala Lumpur, Malaysia; 8Ming Medical Sdn Bhd, Petaling Jaya, Selangor, MalaysiaCorrespondence: Jia Xian Law, Department of Tissue Engineering and Regenerative Medicine, Universiti Kebangsaan Malaysia, Cheras, Kuala Lumpur, Malaysia, Email lawjx@hctm.ukm.edu.myIntroduction: Research has unveiled the remarkable properties of extracellular vesicles derived from mesenchymal stromal cells (MSCs), particularly in promoting wound healing, aiding re-epithelialization, revitalizing aging skin, and inhibiting hyperpigmentation. However, investigations into the potential of small extracellular vesicles from umbilical cord-derived MSCs (UC-MSC-sEVs) in reducing scarring and preventing hyperpigmentation remain limited. Therefore, this study aims to evaluate the impact of UC-MSC-sEVs on the synthesis of the skin’s extracellular matrix (ECM) and pigmentation using in vitro models.Methods: The study investigated the impact of characterized UC-MSC-sEVs on various aspects including the proliferation, migration, antioxidant activity, and ECM gene expression of human dermal fibroblasts (HDF). Additionally, the effects of UC-MSC-sEVs on the proliferation, melanin content, and tyrosinase (TYR) activity of human melanoma cells (MNT-1) were examined. Furthermore, ex vivo models were employed to evaluate the skin permeation of PKH26-labelled UC-MSC-sEVs.Results: The findings indicated that a high concentration of UC-MSC-sEVs positively influenced the proliferation of HDF. However, no changes in cell migration rate were observed. While the expressions of collagen type 1 and type 3 remained unaffected by UC-MSC-sEVs treatment, there were dose-dependent increases in the gene expressions of fibronectin, matrix metallopeptidase (MMP) 1, and MMP 3. Furthermore, UC-MSC-sEVs treatment did not impact the antioxidative superoxide dismutase (SOD) expression in HDF. Although UC-MSC-sEVs did not alter the proliferation of MNT-1 cells, it did result in a dose-dependent reduction in melanin synthesis without affecting TYR activity. However, when it was applied topically, UC-MSC-sEVs failed to penetrate the skin barrier and remained localized within the stratum corneum layer even after 18 hours.Conclusion: These results highlight the potential of UC-MSC-sEVs in stimulating HDF proliferation, regulating ECM synthesis, and reducing melanin production. This demonstrates the promising application of UC-MSC-sEVs in medical aesthetics for benefits such as scar reduction, skin rejuvenation, and skin lightening.Keywords: mesenchymal stromal cell, extracellular vesicles, anti-scarring, pigmentation, medical aesthetic